Impacts of Different Agro-Ecological and Management Practices on the Shrimp Productivity of Ghers in the Southwest Coastal Region of Bangladesh (Progressive Agriculture, 2014)
The study was undertaken to investigate the impacts of water and soil quality parameters, and management practices on shrimp productivity of ghers in three agro-ecological areas of Paikgacha, Shyamnagar and Rampal in the greater Khulna district of Bangladesh. Five ghers of existing culture systems from each of three locations were selected for this study. Findings revealed that water quality parameters including salinity, alkalinity and dissolved oxygen contributed significantly (p